Linguistic variation in the interpretation and production of Italian motion event constructions in younger and older adults: evidence for language change? - Anna Michelotti; Ioli Baroncini; Helen Engemann (Language and Cognition)
Languages vary in the way they encode motion. Following Talmy, languages can be divided into verb-framed (VF, henceforth) or satellite-framed (SF, henceforth), based on how they encode path of motion. However, this difference is not always clear-cut. Italian, for instance, is typically considered a VF language but has also been shown to display a hybrid pattern. Since variation has typically been considered a prerequisite for language change, we investigated whether variation in encoding Italian motion events could indicate incipient language change. We simulated the chain of language change adopting an apparent-time approach and investigated whether the impact of semantic properties (the manner verb’s association with directional motion) on the interpretation and productions of SF Italian constructions was affected by participants’ age. We found that, although this semantic property affects both the interpretation and production of SF constructions, younger participants more readily accepted SF constructions than older participants; this age difference, however, was not significant in the production task. We suggest that these findings might speak for incipient language change, which starts from comprehension and subsequently gradually influences production.